2018 IEEE International Conference on Robotics and Automation (ICRA) 2018
DOI: 10.1109/icra.2018.8461082
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Segmentation from Limited Training Data

Abstract: We present our approach for robotic perception in cluttered scenes that led to winning the recent Amazon Robotics Challenge (ARC) 2017. Next to small objects with shiny and transparent surfaces, the biggest challenge of the 2017 competition was the introduction of unseen categories. In contrast to traditional approaches which require large collections of annotated data and many hours of training, the task here was to obtain a robust perception pipeline with only few minutes of data acquisition and training tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…In 2016, many teams used deep learning to segment objects for the alignment phase, training semantic segmentation networks with separate classes for each object instance on hand-labeled [46] or self-supervised datasets [9]. Team ACRV, the winners of the 2017 ARC, fine-tuned RefineNet to segment and classify 40 unique known objects in a bin, with a system to quickly learn new items with a semi-automated procedure [10,47]. In contrast, our method uses deep learning for category-agnostic segmentation, which can can be used to segment a wide variety of objects not seen in training.…”
Section: Related Workmentioning
confidence: 99%
“…In 2016, many teams used deep learning to segment objects for the alignment phase, training semantic segmentation networks with separate classes for each object instance on hand-labeled [46] or self-supervised datasets [9]. Team ACRV, the winners of the 2017 ARC, fine-tuned RefineNet to segment and classify 40 unique known objects in a bin, with a system to quickly learn new items with a semi-automated procedure [10,47]. In contrast, our method uses deep learning for category-agnostic segmentation, which can can be used to segment a wide variety of objects not seen in training.…”
Section: Related Workmentioning
confidence: 99%
“…After investigating a number of possible approaches, including recent advancements in Deep Metric Learning [12], we found that the best results were obtained by fine-tuning our base RefineNet network on a minimal dataset of the unseen items [13]. Our base RefineNet model was initially trained for 200 epochs on a labelled dataset of approximately 200 images of cluttered scenes containing the 40 known items in the Amazon tote or our storage system.…”
Section: Key System Features a Quick Item Learningmentioning
confidence: 99%
“…An in depth analysis of our RefineNet quick-training approach and a comparison with an alternative Deep Metric Learning approach are provided in [13].…”
Section: Key System Features a Quick Item Learningmentioning
confidence: 99%
“…As recommended in [33], coefficient β 2 could be selected at 0.3. On other hand, β 2 = 0.25 is also frequently used to evaluate the quality of image processing [34]. However, no strong evidence is demonstrated in the literature to prove the priority of 0.25 or 0.3 among other adjacent values.…”
Section: A Probability Map Thresholding Criteriamentioning
confidence: 99%